The Association of DAZ1 Gene Deletion with Azoospermia in Iraqi InfertileMen - Ahmed, Ameen Haider; Altaee, Maha Fakhry (Iraqi Journal of Science, 2024)
A disease of the reproductive system known as infertility is characterized by a clinical pregnancy that cannot be obtained after twelve months or longer of unprotected, ordered sexual copulation. Infertility disorder has impacted the reproductive system when a clinical pregnancy cannot be obtained after twelve months or more of unprotected, ordered sexual interaction. The followinginvestigation was conducted to examine the gene expression levels in Iraqi patients with azoospermia, 150 human blood samples were collected from different regions in Baghdad governorate include (private medicals Labs and the high institute for infertility diagnosis assisted reproductive techniques and Kamal Al- Samara’ay IVF Hospital). The control group consists of 50 sample males with a range of 22-51 years old, while the patient (infertile group) consists of 100 sample males with ages ranging between 25-51 years old, the variations in this gene’s expression between patients and healthy controls were taken into consideration. The age correlation for azoospermia patient’s occurrence compared with controls was studied after subdividing them into subgroups and between patients and controls, there were no discernible differences in terms of age for any of the study groups. The average level of gene expression decreased significantly in this study, according to the findings (ΔCt) of DAZ1 in patient groups compared to the corresponding ΔCt means in the control group (0.12±0.91 vs. 1.45±0.25), also the folding of expression 2-ΔCt of DAZ1 gene in azoospermia groups, reached to (0.39±0.21), which indicating upregulation of this gene in infertile Iraqi men.